2018
DOI: 10.4236/jbm.2018.610007
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-Induced Cognitive Dysfunction is Associated with Increased Oxidative Stress in the Rat Brains

Abstract: High fructose consumption is a risk factor for diabetes. Type 2 diabetes is associated with cognitive and memory impairment. To determine if fructose intake might affect memory function independently of diabetes development, we investigated the effects of monosaccharides on memory in prediabetic state. We examined whether 2.5% apple juice solution could influence cognitive function in salt-sensitive Dahl rats using passive avoidance methods. Furthermore, we examined the role of monosaccharides intake in cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that fructose intake impairs learning and memory in animals, causes brain insulin resistance, neuroinflammation, and reduces neurogenesis by an oxidative stress mechanism (Lowette et al 2015;Spagnuolo et al 2020). Another study showed that fructose reduces cognitive function by a phosphorylation process that disrupts the mitochondria and increases free radicals (Yabe et al 2018). Results from the EPM showed that fructose treated group spent more time in the open arm compared to the fructose+caffeine treated group that spent lesser time.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that fructose intake impairs learning and memory in animals, causes brain insulin resistance, neuroinflammation, and reduces neurogenesis by an oxidative stress mechanism (Lowette et al 2015;Spagnuolo et al 2020). Another study showed that fructose reduces cognitive function by a phosphorylation process that disrupts the mitochondria and increases free radicals (Yabe et al 2018). Results from the EPM showed that fructose treated group spent more time in the open arm compared to the fructose+caffeine treated group that spent lesser time.…”
Section: Discussionmentioning
confidence: 98%